Bentuk Penyajian Color Guard Contest Dalam Pertandingan Grand Prix Marching Band Oleh Komunitas E(x)-Guard Jakarta - Suryo Samudro, Rahmat (Program Studi Pendidikan Tari FBS UNJ, 2023)
Marching band performances consist of musical and visual elements. The visual element in the marching band is predominantly represented by the color guard players. The color guard contributes to the visual effect and conveys the message of the marching band performance. Color guard performances do not always depend on marching band orchestras, they can be independent performances using playback music as accompaniment. The Grand Prix Marching Band 2022 competition featured a color guard contest with one of the participants being the color guard community called E(x)-Guard. Researchers conducted observations, interviews and documentation of the results of the E(x)-Guard performance. This data collection technique led researchers to use descriptive qualitative research methods. A study using a theoretical approach of the basic elements of dance composition by La Meri translated by Soedarsono resulted in the conclusion that the color guard contest performance in the GPMB competition presented by E(x)-Guard with the BICARA repertoire had complete elements.